Bibliometric Analysis Of Overall Equipment Effectiveness (OEE) (Texas Journal of Engineering and Technology, 2026)
Overall equipment effectiveness (OEE) is a key performance indicator used to measure equipment productivity(Overall equipment effectiveness 2008). The purpose of this study is to review and analyze the scientific papers written on OEE(Tang Ho Hwa, Yeo Chiew Tiam, and Ding See Kong 2020). 1377 documents were obtained in the general search; after eliminating duplicates and applying certain inclusion and exclusion criteria, 1308 papers were used for this review. This study provides three main conclusions: During the period 2000-2022, academic interest in this topic has increased and the keywords are maintenance and production, related to the six major losses, lean manufacturing and optimization; a list of authors who have conducted scientific work on the basis of OEE is compiled; and the top 10 countries that conducted scientific work based on OEE are presented based on geographical analysis. VOS viewer software was used to investigate the bibliometric research method and bibliographic display maps(Vinodh 2022; Wudhikarn 2012; Yeo, Chang, and Liu 2021). There are three phases to the bibliometric research process, they are search criteria and source identification, software and data extraction, and then data analysis and interpretation. To our knowledge, several bibliometric comparative reviews on OEE and maintenance have been published. This study serves as a continuation of the above related studies.